The Method of Scriptural Interpretation according to Origen - Anselmus Loba, Klementius (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2024)
The practice of interpreting Scripture by the Church Fathers has become a precious legacy and has significantly contributed to the development of current methods of interpreting Scripture. One of the figures in this context is Origen. This paper explores Origen’s method of scriptural interpretation through observation of his homily on the figure and story of Rahab (Jos 2:1–24) contained in his Homilies on Joshua. The research method used is a literature study. Based on the analysis of his homily on Rahab, it was found that Origen intensely used allegory as a method to convey profound spiritual meaning in interpreting Scripture. In addition, he also combined allegorical with other methods such as typological, Scriptura scripturae interpres, Christological, and ecclesiological. The findings can make significant contributions for Christians today. First, by interpreting the physical violence in the story of Rahab as ‘spiritual violence’, Christians are invited to counteract and prevent the misuse of violent texts in Scripture as motivation and justification for committing wrongdoing. Secondly, by placing Rahab as a symbol of divine love and mercy, Origen shows that all people can belong to the family of God through faith in Jesus, repentance, and good deeds.